Moulds in the kitchen - Clark, Grace Maria (My University, 1892)
Introduction: “Moulds” is an indefinite term applied to minute downy fungi which grow on the surface of matter. These fungi may be either saprophytic or parasitic. They belong to several different divisions, and this makes a description of them difficult to owe with a meager knowledge of fungi in general. Moulds grow on everything, from living plants to old shoes. They propagate by spores so light and small that they are easily carried about by the air and lodged everywhere to remain unobserved till the proper conditions of germination come. These conditions come with warm moist weather, and in such weather, the housekeeper who has cold victuals on hand for a few days finds an abundant crop of these small plants. She finds them occasionally, too, in canned fruit, where the moisture is always present. Four sorts of mould are of common occurrence in the kitchen: Mucar, Eurotium, Penicillium, and Tricothecium roseum. The life history of the first three is known. The last has been studied, so far as I know, only in the conidia bearing stage.
Citation: Clark, Grace Maria. Moulds in the kitchen. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Mold; Mould; Kitchen; Bacteria; Home economics; Bacteriology; Theses; Manuscripts (documents)